Implementasi Model View Controller Pada Aplikasi Pemesanan Makanan Platform Sistem Operasi Android - Cynthia Hayat; Enggalwiguno Rahardja; Frans Pasamboan (STMIK Amik Riau, 2019)
AbstractÂ It is common knowledge in big cities like Jakarta today that to start a small business in the field of food sales can be done quite easily. But to be able to survive, even growing in the midst of market competition, execution of innovations and superior strategies needs to be done. This paper discusses the making of a food ordering application using the mobile-based Object-oriented programming (OOP) method using an android platform that is systematically designed specifically to the characteristics of the object of study. Discovery requirements were carried out by conducting interviews, making scenarios, and ethnographic studies. System Modeling is applied with the UML method through activity diagrams, use-case diagrams, class diagrams and data flow diagrams. Furthermore, adding several features to the needs and demands of stakeholders was fulfilled by combining the MySQL database with Firebase - a Cloud-based platform from Google inc. to integrate the existing mobile user account that is already owned by the user on the device, as well as the utilization of other service facilities that have essential features for future application development. The final results of the study are 2 (two) applications integrated with the android platform, which consist of (1) Food ordering applications for clients (customers) that are expected to facilitate customers in obtaining product information, which further facilitates the purchasing process, and (2) Application management of the food sales process for the admin (seller / owner of the restaurant) and for carrying out additional promotional activities on his business activities.Â Â Keywords : OOP, MVC, Android, Food Ordering